Carbon negative transportation fuels – A techno-economic-environmental analysis of biomass pathways for transportation. (May 2022) - Jasper, Micah; Rafati, Navid; Schimmel, Keith; Shahbazi, Abolghasem; Li, Fanxing; Mba-Wright, Mark; Wang, Lijun
Graphical abstract: Abstract: Global warming and fossil fuel depletion have necessitated alternative sources of energy. Biomass is a promising fuel source because it is renewable and can be carbon negative, even without carbon capture and storage. This study considers biomass as a clean, renewable source for transportation fuels. An Aspen Plus process simulation model was built of a biomass gasification biorefinery with Fischer-Tropsch (FT) synthesis of liquid fuels. A GaBi life cycle assessment model was also built to determine the environmental impacts using a cradle-to-grave approach. Three different product pathways were considered: Fischer-Tropsch synthetic diesel, hydrogen, and electricity. An offgas autothermal reformer with a recycle loop was used to increase FT product yield. Different configurations and combinations of biorefinery products are considered. The thermal efficiency and cost of production of the FT liquid fuels are analyzed using the Aspen Plus process model. The greenhouse gas emissions, profitability, and mileage per kg biomass were compared. The mileage traveled per kilogram biomass was calculated using modern (2019–2021) diesel, electric, and hydrogen fuel cell vehicles. The overall thermal efficiency was found to be between 20 and 41% for FT fuels production, between 58 and 61% for hydrogen production, and around 25–26% for electricity production for this biorefinery. The lowest production costs were found to be $3.171/gal of FT diesel ($24.304/GJ), $1.860/kg of H2 ($15.779/GJ), and 13.332¢/kWh for electricity ($37.034/GJ). All configurations except one had net negative carbon emissions over the life cycle of the biomass. This is because carbon is absorbed in the trees initially, and some of the carbon is sequestered in ash and unconverted char from the gasification process, furthermore co-producing electricity while making transportation fuel offsets even more carbon emissions. Compared to current market rates for diesel, hydrogen, and electricity, the most profitable biorefinery product is shown to be hydrogen while also having net negative carbon emissions. FT diesel can also be profitable, but with a slimmer profit margin (not considering government credits) and still having net negative carbon emissions. However, our biorefinery could not compete with current commercial electricity prices in the US. As oil, hydrogen, and electricity prices continue to change, the economics of the biorefinery and the choice product will change as well. For our current biorefinery model, hydrogen seems to be the most promising product choice for profit while staying carbon negative, while FT diesel is the best choice for sequestering the most carbon and still being profitable.